Peran strategi public relation dalam membangun citra positif perusahaan - Ahla, Hilwiyatul (Maliki Interdisciplinary Journal, 2025)
The strategic role of Public Relations (PR) is becoming increasingly important in building a positive corporate image amidst increasingly fierce global competition and high public transparency. PR serves as a liaison between an organization and its internal and external publics, with the aim of creating mutual understanding, trust, and support. This article synthesizes the results of various studies on several companies in Indonesia, namely Cristal Indonesia Management (CIM), PT Indonesia Comnets Plus (PLN Icon Plus), PT Kilang Pertamina Internasional RU III Plaju, PT ISS Indonesia, and PT Adaro Indonesia. The approach used is a descriptive analysis of the PR strategies implemented by each company in building and maintaining a positive image. The results of the synthesis indicate that the success of PR lies in the integration of two-way communication strategies, the implementation of corporate social responsibility (CSR), rebranding and brand transformation, and the formation of harmonious relations with the public. Consistency, transparency, and sensitivity to public needs are the main factors for the success of PR in strengthening an organization's reputation.